Chorea as the first presenting sign of rheumatic fever in a 12-year-old female child - Kasundra, Mitul N. (International Journal of Contemporary Pediatrics, 2020)
Rheumatic chorea (RC*) is a movement disorder seen in young children and adolescents with a recent history of incompletely treated group A beta-hemolytic streptococcal (GABHS) pharyngitis. Although, it rarely presents as the first manifestation of the rheumatic fever, physicians should be aware of the disease, so that early diagnosis and prompt treatment may lead to elimination of the pathogen and prevent further disease progression. We present a case of a 12-year-old female child who presented with only RC as the first clinical sign.